Spatio-temporal evolution of ground motion intensity caused by reservoir-induced seismicity at the Pertusillo artificial lake (southern Italy) - Picozzi, Matteo; Serlenga, Vincenzo; Stabile, Tony Alfredo (Frontiers in Earth Science, 2022)
We investigate the spatiotemporal evolution of ground motion caused by reservoir-induced seismicity at the Pertusillo artificial lake in southern Italy. The area has a strong seismogenic potential, having been affected in the past by the 1857, Mw 7.0 Basilicata earthquake. We consider ∼1,000 microearthquakes that occurred from 2001 to 2018 and were recorded by a local network of nine seismic stations. The ground motion intensity associated with microseismicity allows us to identify two periods, each lasting approximately 2 years. They are characterized by a high rate of events but exhibit different source properties and spatial distributions. In the first period, the seismicity is spatially clustered close to the lake, on faults with different orientations and kinematics. In the second period, the seismicity is distributed along the Monti della Maddalena faults. Comparing the ground motion intensities of the two periods, we observe that events that occurred in the first period are associated with higher stress levels than others, in agreement with the b-values of the respective frequency-magnitude distributions. We compare the temporal evolution of the ground motion intensity with the rainfall and water levels measured at the artificial lake, as well as with the discharge of a ∼80 km distant spring, which is strictly controlled by climate trends. The results provide information about the regional processes acting on the southern Apennines. Our results show that the microseismicity is clearly associated with the Pertusillo artificial lake in the first period, whereas in the second period is a result of a combination of local effects due to water table oscillations of the lake itself, regional tectonics, and the poroelastic and elastic phenomena associated with carbonate rocks hosting aquifers.